Cross-cultural analysis of teacher confirmation, student motivation, classroom emotion and emotional interest in China, Korea and Japan - Shen, Tingting (2016)
This study investigates the relationship between teacher confirmation and student motivation across three cultures: China, Korea, and Japan and studies how classroom emotion and emotional interest influence this relationship in three different countries. Students in China (n=718), Korea (n=362), and Japan (n=350) completed questionnaires assessing their perceived teacher confirmation, student motivation, classroom emotion and emotional interest. Results of these samples indicate that teacher confirmation is positively correlated with student motivation in Korea and Japan. There is also a significant difference in these three groups on teacher confirmation, emotional support and emotional work. The results showed there was a higher level of responding to questions, interactive teaching style and demonstrating interests in China; a higher level of emotional support and emotional work in Korea compared with China and Japan.